2007
DOI: 10.1210/en.2007-0867
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Prolactin Receptor Messenger Ribonucleic Acid Levels, Prolactin Signaling, and Hyperprolactinemic Inhibition of Pulsatile Luteinizing Hormone Secretion Are Dependent on Estradiol

Abstract: Hyperprolactinemia can reduce fertility and libido. Although central prolactin actions are thought to contribute to this, the mechanisms are poorly understood. We first tested whether chronic hyperprolactinemia inhibited two neuroendocrine parameters necessary for female fertility: pulsatile LH secretion and the estrogen-induced LH surge. Chronic hyperprolactinemia induced by the dopamine antagonist sulpiride caused a 40% reduction LH pulse frequency in ovariectomized rats, but only in the presence of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 1,034 publications
(1,436 reference statements)
2
27
0
Order By: Relevance
“…the concomitant increase in PRLR mrNa expression in the choroid plexus and the plasma PrL concentration during juvenile development suggests that PrLr in the choroid plexus enhances the PrL effect on the induction of maternal-like behavior in juvenile rats. Previously, it was demonstrated that the PRLR mrNa expression level increases to its highest level during lactation in the rat choroid plexus [1,2] and is accompanied by an elevated blood PrL level [2,13]. in our present study, it was observed that the total PRLR and E1 4 -PRLR mrNa levels were much higher on day 3 of lactation compared with in the diestrus state, whereas the E1 3 and E1 5 levels were not increased.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…the concomitant increase in PRLR mrNa expression in the choroid plexus and the plasma PrL concentration during juvenile development suggests that PrLr in the choroid plexus enhances the PrL effect on the induction of maternal-like behavior in juvenile rats. Previously, it was demonstrated that the PRLR mrNa expression level increases to its highest level during lactation in the rat choroid plexus [1,2] and is accompanied by an elevated blood PrL level [2,13]. in our present study, it was observed that the total PRLR and E1 4 -PRLR mrNa levels were much higher on day 3 of lactation compared with in the diestrus state, whereas the E1 3 and E1 5 levels were not increased.…”
Section: Discussionsupporting
confidence: 57%
“…PrL is known to be transported from the blood to the cerebrospinal fluid (CSF) via a PrLr-mediated system in the choroid plexus [37], and PrL enhances its own uptake in the choroid plexus [21]. Many studies have reported an increase in PRLR mrNa levels in the choroid plexus during lactation that correlate with plasma PrL level increases [1,2,13,24,27,30,31,33]. These findings suggest that regulation of PRLR expression in the choroid plexus is critical for PrL action in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that the expression level of Prlr mRNA in the rat choroid plexus increases to the highest level during lactation (Augustine et al 2003, Anderson et al 2008 and is accompanied by a high serum PRL level (Escalada et al 1996, Augustine et al 2003. These findings suggest that Prlr gene expression in the choroid plexus is upregulated by PRL.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, it has been reported that PRL enhances its own uptake in the choroid plexus (Mangurian et al 1992). Supporting this function, a high level of PRLR expression in the choroid plexus has been observed during lactation when the plasma PRL level is also high (Muccioli & Di Carlo 1994, Escalada et al 1996, Sugiyama et al 1996, Pi & Grattan 1999, Augustine et al 2003, Pi et al 2003, Nogami et al 2007, Anderson et al 2008. Also, PRLR expression in this brain region increases during the stress response, accompanying an increase in the plasma PRL level (Fujikawa et al 1995).…”
Section: Introductionmentioning
confidence: 82%
“…Also, the E 2 replacement applied in the present study has been shown to result in equal proestrus-resembling plasma E 2 concentrations in both vehicle- and PRL-treated animals [8]. This is crucial as gonadal steroids were found to influence hypophyseal PRL secretion [51], expression of PRL receptors in the brain [52,53,54], neuronal c- fos stress responses [55] as well as the activity of the OXT system [56,57,58]. However, future experiments are needed to demonstrate if estrogens play a permissive role for the observed effects.…”
Section: Discussionmentioning
confidence: 93%